The Emotional Structure of the Work of Art - Stoškus, Krescencijus (Problemos, 1968)
Art theorists and aestheticists have devoted a good deal of their attention to the analysis of the material, figurative and logical structures of the work of art, while the emotional component has been practically left beyond the boundaries of research, the reason being either that it has been looked upon as un accidental accompaniment of the work of art or as the effect produced or that it is the phenomenon that cannot be detached from the image (idea) and therefore cannot be an object of research. In accordance with certain conclusions of semiotics an attempt is made to describe certain peculiarities of the organisation of the emotional structures of the work of art and from the point of view of communology to describe the specific and conditional character of the emotional information imparted with the help of the system of signs. The paper points out the factors determining the specific peculiarity of emotional in formation tits conditionality) and some extra-semiotic (exciting objects emotions, the regularity of the emotional process) and semiotic (logical and visual structures) limitations of emotional structures.